Legal Analysis of the Imposition of Criminal Sanctions Against Online Gambling Perpetrators From the Perspective of the Electronic Information and Transaction Law - Darma, I Made Wirya; Yasa, I Kadek Dwi Graha Oka (Jurnal Indonesia Sosial Sains, 2026)
This study examines the legal analysis of imposing criminal sanctions on online gambling perpetrators from the perspective of the Electronic Information and Transactions Law (UU ITE). The development of information technology has shifted the modus operandi of gambling from conventional to digital, creating complex legal challenges in criminal law enforcement in Indonesia. The purpose of this study is to analyze the criminal law provisions for online gambling crimes under the ITE Law and to assess the effectiveness of imposing criminal sanctions on online gambling perpetrators. The method used is normative legal research with a statutory approach and a conceptual approach, by adopting primary legal materials in the form of the Criminal Code, Law No. 1 of 2024 concerning the Second Amendment to the ITE Law, as well as secondary legal materials in the form of literature, journals, and related research results. The results of the study indicate that the regulation of online gambling crimes is covered in Article 27, paragraph (2), and Article 45, paragraph (2) of the ITE Law with a maximum prison sentence of 6 years or a maximum fine of IDR 1 billion. However, the effectiveness of law enforcement still faces obstacles in the aspects of evidence, cross-country jurisdiction, and limited resources of law enforcement officers. This study concludes that it is necessary to strengthen regulations, increase the capacity of law enforcement, and coordinate between institutions to increase the effectiveness of imposing criminal sanctions on online gambling perpetrators in Indonesia.